1991
DOI: 10.1099/0022-1317-72-8-1793
|View full text |Cite
|
Sign up to set email alerts
|

A Spontaneous Red Clover Necrotic Mosaic Virus Mutant with a Truncated Movement Protein

Abstract: A spontaneous red clover necrotic mosaic virus mutant, TpM-341, was isolated by multiple passage of Czechoslovakian isolate TpM-34 in beans, followed by three cycles of single lesion isolation in cowpea and in Chenopodium quinoa. The symptoms induced in cowpea by TpM-34 and TpM-341 differed. TpM-34 gave rise to chlorotic lesions which expanded with time, often becoming confluent with adjacent lesions, and developed necrotic margins; the plants became systemically infected. TpM-341 induced necrotic lesions whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…, 1997). Osman et al . (1991) have previously shown that a naturally arising RCNMV mutant, TpM‐341, was capable of cell‐to‐cell and systemic movement in cowpea after deletion of the C‐terminal 88 amino acids of the MP.…”
Section: Introductionsupporting
confidence: 73%
See 4 more Smart Citations
“…, 1997). Osman et al . (1991) have previously shown that a naturally arising RCNMV mutant, TpM‐341, was capable of cell‐to‐cell and systemic movement in cowpea after deletion of the C‐terminal 88 amino acids of the MP.…”
Section: Introductionsupporting
confidence: 73%
“…Local lesions were produced on cowpea, but were smaller than those produced by either CNV or RCNMV. The overall similarity in disease symptoms between ClM5/RM2dd1 and RCNMV supports the notion that the RCNMV MP contains symptom determinants (Osman et al. , 1991; Solovyev et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations